Numerical evaluation of image parameters of ETR-1 - Ahmed Shamim; Krüger Marian; Willomitzer Christian; Zakaria Golam A. (Current Directions in Biomedical Engineering, 2016)
In this work, we developed a method to handle the image quality test-tool precisely. This test-tool is important to evaluate the quality of the medical images for pre-treatment planning phase. But the achieved images are estimated by naked eyes, which does not provide the precise result. Our main goal is to get the desired image parameters numerically. This numerical estimation overcomes the limitation of naked eye observation. Hence, it enhances the pre-treatment planning. The ETR-1 test-tool is considered here. The contrast, the low contrast details and line-pairs (lp/mm) were estimated.